2019
DOI: 10.18186/thermal.540120
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of the Porous Plates on the Tank Bottom on the Boiling Process

Abstract: In the present study, the boiling process is simulated in a fixed-temperature tank using the ANSYS FLUENT commercial software. Eulerian method is used to simulate the condensation and evaporation processes. The effect of porous media on the boiling process is investigated. For this purpose, a porous medium with different porosity coefficients is placed on the bottom of the tank and its effect on the bubble dynamics and wall thermal flux is investigated. The simulation is carried out in two dimensions and is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The heater depends mainly on two basic particles that we find in most devices of this type. It has been updated in this study by incorporating the PCM in the complex to improve and raise productivity and integrating the PCM in the tank to increase the storage capacity and the lack of storage space [5,14,15]. The proposed solar system ( Figure 1) has:…”
Section: Methodology  Thermal Solar System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The heater depends mainly on two basic particles that we find in most devices of this type. It has been updated in this study by incorporating the PCM in the complex to improve and raise productivity and integrating the PCM in the tank to increase the storage capacity and the lack of storage space [5,14,15]. The proposed solar system ( Figure 1) has:…”
Section: Methodology  Thermal Solar System Modelmentioning
confidence: 99%
“…For this reason, the solar heater needs an upgrade at the stage of producing and storing thermal energy. Therefore, there are several ways to manage the thermal energy among these methods, the production and storage of thermal energy by using phase change materials (PCMs) [4,5]. They are materials that can store solar energy as latent heat and become liquid by increasing the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44]. While CFD is an effective tool for numerical study, other numerical study involving ANN may be conducted for enhancing the results, as studies reported earlier have confirmed the same [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 92%
“…Other study involves thermal analysis and multi dimensional modeling of various thermal systems including IC engines, emission dispersion studies, slurry flow, flame study thermal comfort etc. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%